KRITERIA EVALUASI PEMBELAJARAN AL-QUR’AN DENGAN METODE UMMI - Ahmad Akbar Al Faizi; Joko Subando (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
This study aims to examine and formulate evaluation criteria for Quranic learning implemented through the Ummi Method. As a systematic approach to Quranic recitation, the Ummi Method emphasizes tartil (intelligible text), mutqin (intelligible text), and is based on quality standards. However, to ensure its effective implementation, an evaluation instrument appropriate to the method's characteristics is required. This study used a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation studies at educational institutions implementing the Ummi Method. The results indicate that the evaluation criteria for Quranic learning using the Ummi Method encompass three main aspects: (1) cognitive aspects, including mastery of tajweed and makharijul huruf (letter pronunciation); (2) psychomotor aspects, including fluency, accuracy, and aesthetics of recitation; and (3) affective aspects, including attitudes and etiquette toward the Quran. With these criteria, learning evaluation becomes more focused and able to measure learning outcomes holistically. This research is expected to serve as a reference for teachers, institutional administrators, and curriculum developers in improving the quality of Quranic learning based on the Ummi Method.